Long‐term therapy of chronic delta hepatitis with peginterferon alfa - Heller, T.; Rotman, Y.; Koh, C.; Clark, S.; Haynes‐Williams, V.; Chang, R.; McBurney, R.; Schmid, P.; Albrecht, J.; Kleiner, D. E.; Ghany, M. G.; Liang, T. J.; et al. (Alimentary pharmacology & therapeutics, 2014)
Summary Background Chronic delta hepatitis virus (HDV) infection rapidly progresses to cirrhosis. Treatment with peginterferon for up to 2 years is often without durable response. Aim To examine the efficacy and safety of long‐term peginterferon in achieving a durable response. Methods Treatment was initiated with 180 μg/week of peginterferon alfa‐2a with titration to a maximal tolerable dose, for up to 5 years. Liver biopsies and hepatic venous pressure gradients (HVPG) were evaluated at baseline, 1, 3 and 5 years. The primary endpoint was histological improvement or loss of serum HDV and HBsAg at 3 years. Results Thirteen patients were treated for a median of 140 weeks (6–260) with an average peginterferon dose of 180 μg/week (90–270). At baseline, most had advanced disease (median Ishak fibrosis = 3) with portal hypertension (HVPG = 10.2 ± 6 mmHg). Five of 13 patients (39%) achieved the primary endpoint, with three seroconverting for HBsAg after 24, 37 and 202 weeks of treatment. Histological inflammation improved after 1 year, (median HAI: 10 vs. 7, P = 0.01) with persistence in 4/5 patients at 3 years (median HAI: 7.5). Greatest improvements occurred in the first year. Baseline bilirubin and HBsAg levels were significantly lower in virological responders than nonresponders. After 12 weeks, virological responders had a significant decline in HBsAg (1.5 log10 IU/mL, P = 0.05). Conclusion Despite increased doses and duration of therapy, treatment of chronic HDV with peginterferon remains unsatisfactory. Quantitative measures of HBsAg may be an important biomarker of early response to peginterferon therapy in chronic delta hepatitis virus infection.